KONSEP MINDFULNESS DALAM BIMBINGAN DAN KONSELING ISLAM - galuh andina putri (Program Studi Bimbingan dan Konseling Islam, 2021)
Abstract Well-being is the dream of all individuals which will be sought in various ways, both positive and negative. Some individuals do not have the right knowledge so that they take the wrong way and cause their life to be increasingly unhappy, far from the original desired goal. Islamic guidance and counseling is present as a solution to the damage that occurs in society. This process uses various methods and stages with the aim of helping individuals get to know themselves better, understand the truth of life, teach independence in conflict handling skills and bring a spiritual atmosphere that is the soul's need for every human being. The stages that exist require the individual's ability to be fully aware or what is commonly called mindfulness. This full awareness underlies every individual activity in daily life through programs that are accompanied by expert counselors. This awareness helps the individual to consciously feel what is happening to him, what he is thinking, raises a strong intention and desire to change, raises awareness of his God's supervision, helps individuals to be able to evaluate themselves, plan the right steps, can leave everything to God and accept all the decisions of his God with a happy heart. Keywords : Islamic Guidance and Counseling, mindfulness, well-being